Notes on the eastern Cree and northern Saulteaux. Anthropological papers of the AMNH - Skinner, Alanson, 1886-1925. (New York : Published by order of the Trustees [of the American Museum of Natural History], 1911)
1 p. ., p. 1-177. illus., 2 pl. 24 cm.